Altın Madenciliği, Tarihi ve Günümüz: Gümüşhane Örneği - Ferkan Sipahi; Halil İbrahim Zeybek; Enver Akaryalı; İbrahim Çavuşoğlu; Mehmet Ali Gücer (Coğrafi Bilimler Dergisi, 2022)
As in the history of humanity, the need for mines, causing important developments in human life, is gradually increasing. The mines, whose names are given to historical ages, have been a necessary source of raw materials for human beings to survive. Mines are one of the factors that directly affect the country's economy. Gold is a mine whose history is based on ancient history, its production has gained importance especially in recent years as a result of increasing demand and the research for new gold sources. Türkiye is a rich country with a 2% share in the world, with gold deposits of different geological characteristics and 431 ton reserves. Depending on the gold mining in recent years, gold explorations in Türkiye continue intensively and the annual gold production has increased to 39 tons in 2021. It has been determined that gold mining is concentrated in the Aegean and Marmara Regions with the Eastern Black Sea part in Türkiye. Gümüşhane is one of the provinces where gold mining is intense. In this study, the gold mining and importance in Gümüşhane are discussed by giving information about the history of gold mining.